1997
DOI: 10.1074/jbc.272.7.3910
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Inhibition of Silica-induced Tumor Necrosis Factor in Alveolar Macrophages

Abstract: Tumor necrosis factor-␣ (TNF␣) has been shown to play an important role in the pathogenesis of silicotic fibrosis. In this study, antisense oligonucleotides targeted to TNF␣ mRNA were used to inhibit silica-induced TNF␣ gene expression in alveolar macrophages. To achieve macrophage-specific oligonucleotide delivery, a molecular conjugate consisting of mannosylated polylysine that exploits endocytosis via the macrophage mannose receptor was used. Complexes were formed between the mannosylated polylysine and oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…17 The use of antisense oligonucleotides against pro-inflammatory cytokines, or adhesion molecules important in the development of inflammation (interleukin (IL)-1, IL-1 receptor, TNF-␣, ICAM-1) have also been successful in vivo. [18][19][20] Another strategy to protect lung tissue is based on the fact that high levels of toxic, reactive oxygen species are present in the local milieu where acute inflammation is ongoing. In this regard, the transfer of prostaglandin G/H synthase gene has been effective in an experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…17 The use of antisense oligonucleotides against pro-inflammatory cytokines, or adhesion molecules important in the development of inflammation (interleukin (IL)-1, IL-1 receptor, TNF-␣, ICAM-1) have also been successful in vivo. [18][19][20] Another strategy to protect lung tissue is based on the fact that high levels of toxic, reactive oxygen species are present in the local milieu where acute inflammation is ongoing. In this regard, the transfer of prostaglandin G/H synthase gene has been effective in an experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…important role in the pathogenesis of many diseases and elicits a wide range of biological responses, including cell proliferation, differentiation, and apoptosis, depending on the cell type and its state of differentiation (42)(43)(44)(45). We have investigated the tumor promotion activity of TNF-␣ in JB6 Cl 41 cells.…”
Section: Induction Of Cell Transformation By Tnf-␣-tnf-␣ Plays Anmentioning
confidence: 99%
“…With regard to ON, it has been reported that ON, due to their polyanionic nature, poorly permeate the cells to reach their intracellular target sites (17,42). Several research groups (3,29,33,40) also observed that in the absence of appropriate delivery systems, ON exhibited weak or no biological activity, whereas in the presence of delivery systems, e.g., liposomes, ON showed strong activity. In agreement with these findings, our results showed that coadministration of the ON with the liposomal agent DOTAP greatly enhanced the inhibitory activities of ON.…”
Section: Discussionmentioning
confidence: 99%
“…Because TNF-␣ plays an important role in the pathogenesis of a variety of inflammatory and immune diseases, this cytokine has been identified as a key target for pharmacological manipulation (18,33,36,41,45). TNF-␣ is produced principally by macrophages and acts on a variety of immune and nonimmune cells to initiate and amplify inflammatory response (36).…”
mentioning
confidence: 99%